LEARNING SWIMMING SPORTS TO REDUCE FEAR OF WATER FOR CHILDREN WITH A TUNAGRAHITA - Desianti, Mega; Soendari, Tjutju; Abdurahman, Maman (Universitas Pendidikan Indonesia (UPI), 2020)
This research based on the presence of mentally retarded students who feel afraid of water. The purpose of this study was to determine learning swimming sports to reduce student fear. This research is a descriptive study using a survey method. The research data was obtained through a questionnaire using saturated sampling technique because the number of respondents was less than 30 people. The validity test in this study used the product moment formula with r hit r tab (0.352), there were 13 valid items. Reliability test using Cronbach's alpha formula with reliability results of (0.793). Data analysis was performed using descriptive statistics. The results obtained indicate that the response of parents to the research questions is acceptable (positive) with a percentage of (68%). There are obstacles that occur, namely the fearful behavior of students shown during the learning process. However, due to the efforts of students and the solution from the teacher, namely by implementing the introduction of water, students' courage can be formed. It can be concluded that learning swimming sports which is implemented goes well.